Labor characteristics and commitment to work: Exploring occupational well-being - Hermosa-Rodríguez, Angélica-María (Estudios de Administración, 2018)
The main purpose of this study was to examine the relationship between psychosocial job characteristics and work engagement, understanding the latter as an affective-motivational state related to work well-being. To analyze this relationship, the psychosocial characteristics of the work presented in the Demand-Control-Support (DCS) model were taken into account. The possible positive effect that social support has as a moderating variable in the relationship between demands, control and work engagement was also evaluated. This study was cross-sectional, involving 463 workers belonging to companies in the industrial and services sectors. The analysis of the data was carried out using the SPSS 22.0 program and hierarchical linear regression was used to test hypothesized relationships. The results indicated statistically significant associations between control, social support and work engagement; however, this type of relationship was not found between demands and work engagement. The predictive capacity of control and social support on work engagement was evidenced. No moderating effect of social support was confirmed in the relationship between control and work engagement. This study highlights the importance of inquiring about the working conditions that the organization must provide to make work a generator of well-being.